Bahaya dan Masalah-Masalah yang Terjadi pada Remaja dan Implikasi Perkembangan Remaja pada Pendidikan - Ramadhan Lubis; Bahuddin Rozi Lubis; Dwi Retno Anjani; Ersa Nabilla Sufi; Latifah Zahara; Nabila Putri Pratama; Siti Aisiyah Rahman; Yusra Salsabila (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The aim of this research is to find out how language influences and the problems that occur in adolescents and the implications of adolescent development for education. Teenagers' relationships nowadays need to get the main spotlight because in this era of global modernization and the depletion of morals and faith of people, especially teenagers today. All of this is very worrying for the nation because it is in the hands of the younger generation that the nation will be carried, the good and bad of this nation really depends on the young generation